2017
DOI: 10.1186/s12884-016-1217-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe postpartum hemorrhage: a case-control study

Abstract: BackgroundIn high-income countries, the incidence of severe postpartum hemorrhage (PPH) has increased. This has important public health relevance because severe PPH is a leading cause of major maternal morbidity. However, few studies have identified risk factors for severe PPH within a contemporary obstetric cohort.MethodsWe performed a case-control study to identify risk factors for severe PPH among a cohort of women who delivered at one of three hospitals in Norway between 2008 and 2011. A case (severe PPH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
215
3
23

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(285 citation statements)
references
References 39 publications
(38 reference statements)
44
215
3
23
Order By: Relevance
“…Second, there is some evidence that the chronic hypoxic environment caused by anemia can upregulate or dysregulate placental vascularity, which may increase the vulnerability of the placenta and uterus to vascular fragility and PPH. Third, anemia has been associated in some studies, with uterine atony (implicated in PPH), perhaps related to tissue iron deficiency. Fourth, postpartum blood loss of <500 mL (not meeting the standard definitions of PPH), which is the volume of a blood donation and therefore considered inconsequential for nonanemic individuals, may be poorly tolerated in patients with low hemoglobin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is some evidence that the chronic hypoxic environment caused by anemia can upregulate or dysregulate placental vascularity, which may increase the vulnerability of the placenta and uterus to vascular fragility and PPH. Third, anemia has been associated in some studies, with uterine atony (implicated in PPH), perhaps related to tissue iron deficiency. Fourth, postpartum blood loss of <500 mL (not meeting the standard definitions of PPH), which is the volume of a blood donation and therefore considered inconsequential for nonanemic individuals, may be poorly tolerated in patients with low hemoglobin levels.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is congruent with the previous research studies conducted in Thailand that the rates of PPH varied across the hospitals [4,5] There are two mains factors associated with PPH were maternal and health service factors. Some characteristics of women are already known as risk factors of PPH, such as age > 35 years old [6], severe perineum lacerations [26], anemia and multiple pregnancy [11]. However, these variables were not predictive factors for PPH in this study except they showed history of PPH and delivered a baby with a weight of more than 3500 g. The findings reveal that those women who experienced PPH are more likely to have increased the odds of PPH than those without, this congruent with previous studies that past history of PPH is associated with PPH [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, complications during pregnancy, such as pregnant women with diabetes mellitus [9] and pregnant women with chronic anemia [6,10] appear to also increase the risk of PPH. Women with a past history of PPH were more likely to experience PPH than others [11]. Obstetric factors are another compounding factors that increase the risk for PPH; such as multiple pregnancy [12,13] and the baby weight of 4000 g or more [14].…”
Section: Introductionmentioning
confidence: 99%
“…The increase of severe PPH is not due to changes in risk factors over time, but to an unexplainable higher incidence of uterine atony 213,218,219 . However, recently previous severe PPH is found to be the strongest independent risk factor in addition to retained placenta tissue on the risk of severe PPH 321 . The increasing rates of abnormal placentation are associated to increasing cesarean section rates affecting the risk of near miss cases and the maternal morbidity 322,323 .…”
Section: Postpartum Hemorrhagementioning
confidence: 86%